2001
DOI: 10.1016/s1097-2765(01)00336-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential Dimer Activities of the Transcription Factor Oct-1 by DNA-Induced Interface Swapping

Abstract: Two crystal structures of Oct-1 POU domain bound to DNA provide a rationale for differential, conformation-dependent recruitment of transcription cofactors. The POU-homeo and POU-specific subdomains of Oct-1 contain two different nonoverlapping pairs of surface patches that are capable of forming unrelated protein-protein interfaces. Members of the POU factor family contain one or two conserved sequence motifs in the interface that are known to be phosphorylated, as noted for Oct-1 and Pit-1. Modeling of Oct-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
169
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(177 citation statements)
references
References 36 publications
7
169
1
Order By: Relevance
“…1B). We were therefore interested in whether the observed different biochemical properties of the POU/ HMG complexes formed on the two enhancers could be attributed to this different spacing of the binding sites, similar to the earlier example of POU factor dimerization (Tomilin et al 2000;Reményi et al 2001b). In our previous studies, we have shown that the transcriptional activity of POU factor dimers is regulated by alterations in their quaternary arrangement, which are induced by binding to specific regulatory elements of target genes (Tomilin et al 2000;Reményi et al 2001b).…”
Section: Oct4 and Sox2 Interact Differentially On The Fgf4 And Utf1 Ementioning
confidence: 84%
See 1 more Smart Citation
“…1B). We were therefore interested in whether the observed different biochemical properties of the POU/ HMG complexes formed on the two enhancers could be attributed to this different spacing of the binding sites, similar to the earlier example of POU factor dimerization (Tomilin et al 2000;Reményi et al 2001b). In our previous studies, we have shown that the transcriptional activity of POU factor dimers is regulated by alterations in their quaternary arrangement, which are induced by binding to specific regulatory elements of target genes (Tomilin et al 2000;Reményi et al 2001b).…”
Section: Oct4 and Sox2 Interact Differentially On The Fgf4 And Utf1 Ementioning
confidence: 84%
“…In this study, we investigate the interaction of Oct1 and Oct4 with Sox2 on two different DNA enhancers to test whether a previously discovered regulation mechanism of DNA-mediated swapping of the arrangement of homodimers (Tomilin et al 2000;Reményi et al 2001b) may also be applicable for unrelated transcription factor assemblies. We first solved the crystal structure of the ternary Oct1/Sox2/FGF4 enhancer element complex and then used homology modeling tools to construct an Oct4/Sox2/FGF4 as well as an Oct4/Sox2/UTF1 structural model.…”
mentioning
confidence: 99%
“…The alignment was prepared in T‐Coffee software and colors distinguish conservation and amino acid residue types. A protein surface interacting with the MORE DNA (as shown in 17) is highlighted. Each of three studied residues (B) is marked by a black asterisk.…”
Section: Resultsmentioning
confidence: 99%
“…Second, we chose a double mutant in the first alpha helix of the Oct4 POU S subdomain (Oct4 7D,22K ) previously shown to be required for maintaining pluripotency 43. Third, a double mutation that completely abolishes Oct4 interaction with Sox2 on canonical SoxOct elements was generated 17 (Oct4 21Y,29R ). Fourth, the POU domain linker of Oct4 was replaced by that of Oct6 (Oct4 LinkO6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation